Predicting School Burnout Based on Reward Addiction in Academic Contexts in High School - Ayşe Aypay (Sakarya University Journal of Education)
It is hypothesised that reward addiction in the academic context causing dependence to the outside world in experiencing the feeling of pleasure and no-reward clues leading to stress as well as negative feelings and behaviours in students can be related to school burnout that is caused by long-term stress factors at school. For this reason, this study aimed to determine whether high school students' reward addiction was a significant predictor of the school burnout syndrome they experienced. The participants were 265 students who were studying at 9th, 10th and 11th grades at two state high schools in Eskişehir. Reward Addiction Scale for High School Students, and School Burnout Scale For High School Students were employed to gather the data. Multiple Linear Regression Analysis was conducted to analyse the data gathered. The analyses revealed that reward addiction in the academic context predicted high school students' school burnout at a weak level. Reward addiction in the academic context explained the variances in burnout due to family and being bored and tired of teacher attitudes to a higher extent compared to other burnout dimensions. It is thought that the findings of this study are of significance since it introduces a variable that is a predictor, although at a weak level, of school burnout to the literature.